ANALISIS KONFLIK PEMBANGUNAN NEW YOGYAKARTA INTERNATIONAL AIRPORT - Muhammad Alhada Fuadilah Habib; Mukhammad Fatkhullah; Siti Muslihatul Mukaromah; Ayla Karina Budita (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2022)
The need for air transportation in the modern era as it is today is proven to continue to increase significantly. This increase is seen as an opportunity by PT. Angkasa Pura to carry out the construction of a new airport in Yogyakarta. The construction of this airport is welcomed by the Yogyakarta government because it is seen as being able to improve the welfare of the community. However, quite a lot of people are against the construction of this airport for various reasons. This study focuses on efforts to trace the root causes of the conflict in the construction of the New Yogyakarta International Airport (NYIA), identify the actors involved in the conflict, identify the forms of conflict that occur, and identify the social and economic impacts for the Kulonprogo community. The research method used is descriptive qualitative with data mining techniques in the form of observation, in-depth interviews, FGD, and literature studies. The results of this study found that the root cause of the phenomenon of conflict over the construction of the New Yogyakarta International Airport (NYIA) actually occurred due to differences in interests and also different perspectives in the management of natural resources on land in Kulonprogo. Some use the ecofeminism paradigm, some use the capitalist paradigm. This difference then gave rise to conflict between the government-business side and civil society parties who refused to build the airport. Various attempts were made by the community to resist by forming an organization called Wahana Tri Tunggal (WTT) with various forms of resistance social movements in it. The development of the NYIA in turn gave rise to vulnerable groups of people whose survival was threatened because their land as a place to live and their main livelihood was used as an airport. These vulnerable people really need attention and assistance, especially from the government to be able to survive in their new conditions.